Knockout of Dopamine D3 Receptor Gene Blocked Methamphetamine-Induced Distinct Changes of Dopaminergic and Glutamatergic Synapse in the Nucleus Accumbens Shell of Mice - Wang, Shuai; Li, Ming; Su, Linlan; Wang, Yu; Ma, Dongliang; Wang, Hongyan; Zhu, Jie; Chen, Teng (Frontiers in Cellular Neuroscience, 2022)
Structural plasticity changes in the brain are thought to underlie, at least partially, drug-induced persistent changes in behavior. Our previous study reported that increased synaptic density in the nucleus accumbens shell (NAcsh) correlates with and may contribute to behavioral sensitization induced by methamphetamine (METH). However, the distinct changes of dopaminergic and glutamatergic synapses and the modulating effects of dopamine D3 receptor remain unclear. In the current study, we used immunohistochemistry electron-microscopy and immunofluorescence to detect the changes of dopamine D1, D2 and glutamate NR2B positive synapses and cells in the NAcsh of METH-sensitized wild-type (WT) and knockout of dopamine D3 receptor gene (D3-/-) mice. We found that METH induced long-term behavioral sensitization in WT mice, which was accompanied by an increased number, rate of dopamine D1 receptor positive synapses and cells, as well as glutamate NR2B positive synapses and cells. In contrast, the number and rate of dopamine D2 receptor positive synapses and cells were significantly decreased in the NAcsh of METH-sensitized WT mice. D3-/- mice exhibited attenuated acute locomotor responses and behavioral sensitization to METH compared to WT mice. Moreover, the knockout of dopamine D3 receptor gene inhibited METH-induced the changes of dopaminergic and glutamatergic synapses in the NAcsh of METH-sensitized mice. Taken together, our results suggest that METH induced distinct changes of dopaminergic and glutamatergic synapses and cells in the NAcsh of mice, which was blocked by the knockout of dopamine D3 receptor gene, and may contribute to, at least partially, METH-induced behavior sensitization as well as the modulating effect of the dopamine D3 receptor.